PENERAPAN DESAIN KELAS EFEKTIF BAGI ANAK BERKEBUTUHAN KHUSUS DI SNETS YCHI AUTISM CENTRE CABANG JEPARA - Murni, Sri; Naiema, An Naas Shahifatun; Suhaila, Arina; Sanjali, Sarwan; Rizka, Muhammad Dany; Shofiyuddin, Muhammad; Zulfahmi, Muhammad Nofan (UNIVERSITAS PGRI MADIUN, 2022)
Abstract. In each child there is an ability or potential that is unique to him or her. And child rights which state that all children have the same rights and obligations to live and develop fully according to their potential. Autistic children generally have a high level of carefulness in terms of visualization. This sensitivity to visualization is traumatic to certain colors. the study room is designed according to the characteristics of the behavior of children with special needs or according to the type or type of therapy.